2016
DOI: 10.1016/j.bj.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic outcome of necrotic immature teeth treated with two endodontic techniques: A retrospective analysis

Abstract: BackgroundThe endodontic treatment of teeth with immature root has always been a challenge. To achieve a better prognosis, regenerative endodontic treatment may become a treatment trend for teeth with apical periodontitis and immature roots.MethodsClinical and radiographic data were collected from 38 endodontic treated immature teeth (21 apexification and 17 regeneration). Measure the radiographic outcome by quantifying the apical lesion.ResultsThere was no statistical difference between the two treatments reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 16 publications
2
37
0
1
Order By: Relevance
“…In a retrospective study, based on PAI scores, Chen et al. (23) detected no significant difference in healing following apexification treatments performed using CH and MTA at the end of 1, 3, 6 and 12 months follow‐up periods. In contrast to these findings, Moretti et al.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, based on PAI scores, Chen et al. (23) detected no significant difference in healing following apexification treatments performed using CH and MTA at the end of 1, 3, 6 and 12 months follow‐up periods. In contrast to these findings, Moretti et al.…”
Section: Discussionmentioning
confidence: 99%
“…Another purpose is blood clot formation, which may act as a scaffold [51]. Most of the available data indicated that intracanal bleeding plays a key role in pulp-dentin complex repair [127], however, some studies have demonstrated that cases with the tissue laceration step omitted had successful outcomes as well [127,128]. Palma et al [129] showed that using blood clotting in the treatment protocol resulted in improved healing outcomes, formation of dentin in the root canal, and also vascularized tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies included in this systematic review were of a retrospective cohort (n = 5) 12,14,15,17,21 . Meanwhile, the study by Lin et al 19 was a randomized clinical trial and the study by Nagy et al 20 was a non-randomized clinical trial.…”
Section: Type Of Studymentioning
confidence: 99%